Implementasi Landasan Sosiologi dalam Meningkatkan Mobilitas Sosial di SMAN 1 Kaliorang - Nurazizah, Eva; Nurwana, Nurwana; Yasin, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
Education is a complex social phenomenon influenced by various social, cultural, and economic factors. It cannot be separated from sociology, which studies society. This is because education has the ultimate goal of advancing society. Therefore, the sociological foundation becomes an important component to be studied and applied in education. This article elaborates on the sociological foundation in education, the goals and functions of sociological foundation in education, as well as society's views on education as observed from State Senior High School 1 Kaliorang. The aim of this article is to enhance understanding and implementation of sociological foundations in education to create a unified identity in teaching towards improvement. The article is investigated through qualitative methods including interviews, documentation, and observation, which are then organized according to critical analysis to obtain appropriate data. The research results itself show positive impressions regarding the success of the researched school in integrating sociological foundations into its educational system despite being in a multicultural environment.